Melanesian geo. (Suva, Fiji ; Honiara, Solomon Is. : Melanesian geo, Journal of Society and the Environment in Melanesia, 2005)
Melanesian Geo is a grassroot magazine of society and the environment in Melanesia. It is also a student initiated environment magazine in Fiji and Solomon Islands.
Description based on: no. 4 (2007)
Also issued electronically on the publisher's website. Address as at 21 Feb. 2007: http://www.melanesiangeo.com/index.html
Keywords: Ecology -- Melanesia -- Periodicals; Environmental policy -- Melanesia -- Periodicals; Community development -- Melanesia -- Periodicals; Human geography -- Melanesia -- Periodicals; Geography -- Melanesia -- Periodicals; Melanesia -- Periodicals